Peningkatan Branding Produk Melalui Sosial Media pada UMKM Barley - Trilaksono, Teddy; Cynthia, Michelle; Goestiadji, Daniel Jonathan; Tjitra, Bernard; Chandra, Cherill; Burhan, Miguel Alejandro; Emmanuel, Debora; Jonathan, Garren; Tanjaya, Katherine (Journal Pemberdayaan Masyarakat Indonesia, 2024)
Barley is a type of grain that comes from the wheat family. Barley is widely used as a raw material in bread, drinks, and various other dishes. Barley can lower blood sugar, blood pressure, and cholesterol, and aid weight loss. In Indonesia, barley was once commonly consumed by the Dayak people. They process barley into rice, porridge, and cakes. Barley was then developed by the government of East Kalimantan, namely Gunawan Setyobudi, who is an extension worker at the Agricultural Fisheries and Forestry Extension Center (BP3K) Loa Kulu Kukar District. Barley planting has been carried out since 2008 and cultivation and plant development have been carried out since 2013. The benefits of plants are very good and have great benefits for consumers who do health therapy or diet. However, this barley is less well known by other Indonesian people. Not many know that barley exists. With social media, artisans can increase the branding of barley products so that barley products can be increasingly recognized by other Indonesian people. Overall, social media is very helpful to the community because it can promote processed barley products and attract public interest in processed barley products. The existence of social media is expected to help increase public knowledge of processed barley products so that barley will become even more well known to many people.